TEMPS‐A (short version) plays a supplementary role in the differential diagnosis between major depressive disorder and bipolar disorder. Issue 5 (5th February 2021) - Morishita, Chihiro; Kameyama, Rie; Toda, Hiroyuki; Masuya, Jiro; Fujimura, Yota; Higashi, Shinji; Kusumi, Ichiro; Inoue, Takeshi
Abstract : Aim: Early differential diagnosis between patients with major depressive disorder (MDD) and bipolar disorder (BD), and subsequently providing appropriate treatments are essential. There has been increased interest regarding the association between affective temperaments and mood disorder diagnosis. Our aim was to analyze the diagnostic validity of affective temperaments assessed by the short version of the Temperament Evaluation of Memphis, Pisa, Paris and San Diego‐autoquestionnaire version (TEMPS‐A), in mood disorder patients. Methods: Inpatients with MDD ( n = 146) or BD ( n = 128) completed the short version of TEMPS‐A, and their depressive and manic symptom severities were evaluated. Data of MDD and BD patients were compared by univariable and multivariable analyses. Results: Of the five affective temperament dimensions, substantially higher hyperthymic, irritable, and cyclothymic temperament scores were found in BD patients than in MDD patients. Using a multivariable logistic regression model built using the severities of depressed and manic conditions, and the five affective temperament subscale scores as independent variables, we identified two factors statistically associated with BD diagnosis (anxious temperament and cyclothymic temperament). The recommended cutoff point for the 12 items evaluating cyclothymic temperament to differentiate BD from MDD was 8 or more 'True' items (sensitivity: 35.9%, specificity: 87.7%). Limitations: Our design was cross‐sectional, and therefore, there was a possibility of longitudinal diagnostic conversion of patients from MDD to BD. Conclusion: Cyclothymic and anxious temperaments on the short version of TEMPS‐A, identified as diagnostic differentiating factors between MDD and BD, may play supplementary roles in the early identification of BD.